PENGEMBANGAN INSTRUMEN TES DIAGNOSTIK KOGNITIF PADA MATERI EKOSISTEM DI KELAS X SEKOLAH MENENGAH ATAS - Sinta, Sinta; Kurnia Ningsih; Anisyah Yuniarti (Universitas Muhammadiyah Pontianak, 2025)
This study aims to develop a cognitive diagnostic test instrument that is suitable for use in identifying the cognitive abilities of grade X students of Senior High School on Ecosystem material. This study uses the Research and Development (R&D) method with the 4D development model of Thiagarajan (1974) (Define, Design, Develop, and Disseminate) which is limited to the Develop stage. The test development procedure is adjusted to the stages of test development according to Mardapi (2008), which consists of 9 stages, in this study the test development stage is limited and adjusted to the needs of researchers, namely up to 6 stages only consisting of 1) preparing test specifications, 2) writing tests, 3) reviewing tests, 4) conducting test trials, 5) analyzing test items, and 6) improving tests. The research subjects were 75 students from three schools, namely SMA Negeri 01 Salatiga, SMA Negeri 01 Selakau, and SMA Negeri 02 Selakau who were selected using a purposive sampling technique. The developed cognitive diagnostic test instrument can be used as a reference for teachers in compiling valid and reliable cognitive diagnostic test instruments and as an alternative for teachers to find out the learning needs of each student in the cognitive aspect of ecosystem material. Data were collected through interviews, validation sheets, and test instrument sheets. The instrument developed consisted of 25 multiple-choice questions designed to measure students' cognitive understanding before learning. The results of the content validity analysis using Aiken's V obtained an average coefficient of 0.97, indicating that all items were valid in terms of material, construction, and language. The inter-rater reliability analysis using the Intraclass Correlation Coefficient (ICC) produced a value of 0.411, which is included in the fairly good category. The item validity analysis showed 20 valid items and 5 invalid items. Based on these results, the 20 items of the cognitive diagnostic test instrument developed were declared valid, reliable, and suitable for use as an assessment tool to identify students' cognitive abilities in the Ecosystem material.